ChemInform Abstract: Pd‐Catalyzed α‐Arylation of α, α‐Difluoroketones with Aryl Bromides and Chlorides. A Route to Difluoromethylarenes. Issue 44 (4th November 2014) - Ge, Shaozhong; Chaladaj, Wojciech; Hartwig, John F.
Abstract A convenient and efficient protocol for the coupling of α, α‐difluoroketones with aryl bromides and chlorides is described.